TRANSFORMATION OF THE STRUCTURE OF HUMAN CAPITAL IN THE CONTEXT OF WAR SHOCK (INNOVATIVE ECONOMY, 2025)
Chernenko D.Ye. TRANSFORMATION OF THE STRUCTURE OF HUMAN CAPITAL IN THE CONTEXT OF WAR SHOCKPurpose. The aim of the article is to identify the specifics of the impact of war shock on the structure of human capital and revealing transformational changes in its main components. Methodology of research. The methodological basis consists of a systematic approach, structural and functional analysis, comparative analysis, and a method of socio-economic diagnostics for assessing transformations in the sphere of human capital under the influence of war. Content analysis of analytical reports of international organisations, national statistical data, regulatory and legal documents of Ukraine, as well as scientific works devoted to the impact of armed conflicts on demographic and market-labour processes was used. The empirical base was formed on the basis of official indicators of migration, employment, educational losses, and demographic dynamics. Findings. It has been established that the war shock has a systemic and multidimensional impact on the structure of human capital, disrupting the established mechanisms of its formation, reproduction, and use. A summary of the results presented in a comparative matrix and structural diagram indicates simultaneous demographic, educational, professional, sectoral and social shifts caused by migration processes, labour market deformation, employment transformation and deterioration in the health of the population. It has been found that these changes are interrelated and manifest themselves with varying intensity depending on regional conditions, sectoral specialisation and the institutional capacity of the economy. The war simultaneously exacerbates the loss of human potential and initiates processes of forced adaptation that change the structure of skills and professional trajectories. In this context, the transformation of human capital takes on not only a destructive but also a structure-forming character, shaping new requirements for the quality of the workforce. The combination of these changes forms a new configuration of human potential, in which the importance of adaptability, mobility, digital competencies and the ability to quickly reorient oneself professionally is growing.Originality. The interpretation of human capital transformation processes in conditions of military shock as a systemic process combining increased structural risks and adaptive shifts has been further developed. The impact of military shock on human capital has been identified, taking into account demographic, educational, professional, sectoral and socio-psychological components, which, unlike existing approaches, allows for a more comprehensive interpretation of transformation processes in crisis conditions.Practical value. The results obtained can be used in the formation of state policy on the restoration and modernisation of human capital in the fields of education, health care, regional development, the labour market and migration policy. The research materials are useful for the development of retraining programmes, demographic recovery strategies, regional reconstruction plans and comprehensive mental health support measures.Key words: human capital, war shock, migration, employment, demographic change, educational losses, occupational structure, population health, labour market, post-war recovery.
Keywords: human capital; war shock; migration; employment; demographic change; educational losses; occupational structure; population health; labour market; post-war recovery